The protection of reinforced concrete structures: Active and passive systems - Christian Paglia (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
The conservation state, maintenance, repair, and complete restoration of reinforced concrete structures are recurring actions necessary to preserve the built infrastructure. A big issue related to enormous costs aimed at extending the service life of construction systems and addressed to sustainability. In the investigated cases of buildings and civil engineering structures, active and passive protection methods are presented. Both exhibit advantages and disadvantages that need to be accurately studied in order to make a correct and durable choice. Generally, active systems are often used in harsh environmental conditions, where more forms of localized corrosion take place, while passive methods are often utilized where the degradation and the structures are less adversely affected by intense degradation phenomena.